THE INFLUENCE OF DIFFERENT DRYING DURATIONS ON THE MOISTURE CONTENT AND PROTEIN CONTENT OF PUMPKIN FLOUR (CUCURBITA MOSCHATA) - Rahmawati, Sri; Putri, Rizky Febriyani; Hafizah, Ellyna (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2022)
Pumpkin (Cucurbita moschata), also known as waluh (banjar) and pumpkin parang (Java), is one of the local foods with high nutritional value beneficial for the human body. Cultivated pumpkin has a shorter shelf life than whole pumpkin, requiring processing into flour to enhance its longevity and prevent damage. This study aimed to determine the effect of different drying times using an oven on protein content and water content in pumpkin flour. The research was conducted at the ULM Banjarmasin Science Laboratory using the Completely Randomized Design (CRD) method with five treatments and three replicates. The flour was produced in the IPA Laboratory of ULM Banjarmasin using various drying time variations with the Completely Randomized Design (CRD) method involving five treatments and three replicates. Parameters assessing the differences in flour included protein content and water content. The test results, analyzed with ANOVA, revealed that the processing of pumpkin flour with different drying times significantly affected the protein and moisture content of the flour. The highest protein content, 24.98%, was found in the T2 treatment involving drying in an oven for 2 hours, while the T5 treatment, drying for 3.5 hours, showed the highest water content at 12.46%.